Influenza A and the Role of the Media in a Pandemic: What Social Representations Create the Media about Health Epidemics? - Idoiaga Mondragón, Nahia (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2014)
This paper analyzes the social representations of the pandemic influenza A (H1N1) and their influence on the treatment made by the media during the crisis. The research takes as geosocial space analysis Mexico (where swine flu started) and Spain from March 2009 to August 2010. The analysis focused on the two general newspapers with the largest circulation in each country (El Universal and El País). This research intertwine two theoretical frameworks: Framing theory and the Colective Symbolic Coping (CSC) on social representations. The results show that the development of the health crisis influenced the use of key interpretive frames by the media, that launched the CSC process. Finally, the theoretical and applied implications of the interrelationship between the two theoretical perspectives used in the workplace are discussed.